The cyber presence of Babri Masjid: history, politics and difference in online Indian Islam - Chopra, Rohit (2008)
Although the demolition of Babri Masjid predates the invention of the worldwide web and the growth of internet usage in India, in online India Muslimm discourse "Babri Masjid" serves as a focal point for articulating Indian Muslim identity. The cyber presence of Babri Masjid mediates competing historical narratives about Indian Islam, the political discourse of secular and constitutional citizenship, and questions of minority rights and religious difference. This paper describes some of the modes in which Indian Muslims use the internet to negotiate and express identity claims. - Reproduced.
Keywords: Babri Masjid; Islam; Moslems; Mosques